The Complete Gardener - Intorduced by Titchmarsh, Alan (London Whsmith, 1990)
This comprehensive volume provides all the information and guidance amateur gardeners will need on how to design, plant and maintain a garden, whether it is an open site, a small town garden or a tiny urban patio. The sections include creating a garden, gardening under glass and the garden year.
Include Index and Illustration
Keywords: Gardening